Unusual Location: Omental Ectopic Pregnancy Killing Me Slowly - Rendy Singgih; Tamara, Yosi (Indonesian Journal of Obstetrics and Gynecology, 2024)
Objective: Omentum pregnancy is an ectopic pregnancy in the abdominal cavity. The event has high morbidity and mortality. The purpose of this case is to present a rare case of abdominal ectopic pregnancy that occurred in a young woman. Methods: Case report. Results: A 22-year-old woman at 16 weeks gestation presented with abdominal pain and clinical shock. Examination results revealed pregnancy outside the womb, with an estimated fetal weight of 193 grams and positive heart activity. The patient underwent laparotomy surgery, revealing that the pregnancy had occurred in the omentum organ with placental attachment. Conclusion: In this case, emergency management began with the patient's reception in the emergency department, followed by laparotomy exploration. After a meticulous surgery, the pregnancy's location was identified in the omentum, and the evacuation of pregnancy products was performed. The patient received treatment for several days until being discharged home. Early diagnosis and interprofessional management are crucial if similar conditions are suspected in the future to prevent morbidity. Keywords: abdominal cavity, ectopic pregnancy, omental pregnancy